SUPERPOSITION OF "ALASKAN" AND "CHINESE" MODELS OF PALEOCLIMATE RECORDS IN MAGNETIC PROPERTIES OF UPPER AND MIDDLE NEOPLEISTOCENE DEPOSITS IN SOUTHERN WEST SIBERIA - Matasova G.G.; Kazansky A.Yu.; Zykina V.S. (My University, 2003)
Rock-magnetic studies of the Belovo key loess-paleosol section (52.4° N, 83.4° E) have shown that the loess accumulation and soil genesis on the Ob' Plateau were affected by a specific regional paleoclimate. During the periods of loess formation corresponding to periods of cooling, the main factor responsible for the increased magnetic properties of loess was the force of wind transporting products of disintegration and weathering of rocks with abundant magnetic material. In the periods of warming, the wind attenuation led to a decreased supply of clastic and magnetic material and to weaker magnetic properties of paleosols to follow the "Alaskan" model. During the interglacials, the climatic conditions were warm and wet enough to favor the enrichment of the rocks of soil complexes in fine-grained magnetic fraction according to the "Chinese" type. Thus, the magnetic properties of the loesses and paleosols of southern West Siberia display the superposition of two known types of record of paleoclimatic fluctuations.
Keywords: Magnetic properties; loess-paleosol deposits; paleoclimate; West Siberia; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен